Nonadiabatic microfiber based mode-locked erbium-doped fiber laser using graphene - Sulaiman, Azlan; Harun, Sulaiman Wadi; Ahmad, F.; Ahmad, Harith (John Wiley & Sons, 2014)
A new compact and low threshold mode-locked Erbium-doped fiber laser (EDFL) using nonadiabatic microfiber in conjunction with a graphene saturable absorber is demonstrated. The graphene was synthesized by electrochemical exfoliation of graphite at room temperature in 1% sodium dodecyl sulfate aqueous solution. Graphene flakes obtained from the process are mixed with polyethylene oxide as the host polymer to produce composite solution which acts as passive mode locker in the EDFL linear cavity. Mode-locked laser, with a threshold of less than 10 mW, pulse repetition rate of 55.8 MHz, and pulse duration of 0.82 ps, is achieved. The EDFL operates at around 1531.8 nm with an average output from 0.1 mW, pulse energy of 2 pJ at the 980 nm pump power of 10 mW.